Pengendalian Intern Merupakan Bagian Integral Organizational Governance Pada Perguruan Tinggi Negeri - Eni Wuryani (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2010)
AbstractInternal control form try activity for guarantee objective achievement and organization target. Internal Audit Financial (IAF) a certain integral share from effective governance process. Organizational governance can dictatorial if university make internal monitoring regular before external monitoring that is accreditation. Arranged monitoring in type continue audit internal with review management system can guarantee a university can continue make quality improvement.